The parent-offspring microbiome and neurobehavioral development. (2019) - Alberts, Jeffrey R.; Harshaw, Christopher; Demas, Gregory E.; Wellman, Cara L.; Morrow, Ardythe L.
Abstract: We identify the significance and typical requirements of developmental analyses of the microbiome-gut-brain (MGB) in parents, offspring, and parent-offspring relations, which have particular importance for neurobehavioral outcomes in mammalian species, including humans. We call for a focus on behavioral measures of social-emotional function. Methodological approaches to interpreting relations between the microbiota and behavior are discussed.